Coping Stress dalam Pendidikan Islam Perspektif Neurosains: Strategi Siswa Menghadapi Ujian Sekolah: STRATEGI SISWA MENGHADAPI UJIAN SEKOLAH - Rizky Hanifah; Suyadi Suyadi (Universitas Islam Lamongan, 2024)
Examinations are one of the methods teachers use to assess students' abilities in achieving specific learning objectives. However, it is not uncommon for students to experience anxiety or stress when facing exams. Literature reveals that students experience stress at varying levels, from mild to severe. This research is a qualitative study based on library research. The data sources are derived from publications of articles in Sinta-indexed scientific journals. The findings of this research show that students' stress coping mechanisms in facing exams, within the perspective of Islamic education neuroscience, include increasing worship and studying, especially in the last third of the night, good time management, and ensuring a comfortable and conducive study environment. The optimal brain condition for learning is at the alpha wave level. Study sessions also need not be too long to prevent brain fatigue. Ice breaking can be an effective alternative to refresh the brain when it starts to feel fatigued. By considering these factors, students can minimize stress and be better prepared to face exams.